Education and science: current trends - Krapostin A. A., Vereshchaka A. S., Sotova E. S., Vereshchaka A. A., Krasnovskii A. N., Chuyan E. N., Ravaeva M. Y., Baranov G. V., Yusupova L. G., Kireeva N. A., Redko A. M., Shutenko E. N., Alekseeva E. S., Demidenko L. L., Saltykova M. V., Starygina S. D., Nuriev N. K., Zhdanova S. N., Bespalova V. V., Polianskaia O. A., Kadyrova O. V., Domanska L., Chmyreva M. I., Drozhzhina N. B. (Education and science: current trends, 2016)
modern society increasingly places demands on the education system, the level of quality. At present, the education system is undergoing dramatic changes, but still faces some problems that inhibit the interaction of education with production and science. The article discusses the existing problems of education, discussed innovative ways to address them, as well as the ways of interaction between the educational process and production.
Keywords: интерактивные методы; инновационное образование; методы образования; функции науки; институт образования; innovative education; methods of education; interactive methods; functions of science; Institute of Education